Acute fibrinous organising pneumonia presenting as a cavitary lung lesion and treatment response to azithromycin. Issue 8 (21st August 2019) - Aslam, Waqas; Perez-Guerra, Francisco; Jebakumar, Deborah; Culver, Daniel A; Ghamande, Shekhar
Abstract : Acute fibrinous organising pneumonia is distinct from the classic diffuse alveolar damage, organising pneumonia and eosinophilic pneumonia. A 52-year-old woman presented with fever, productive cough, night sweats and left-sided pleuritic chest pain for a week. Physical examination was significant only for decreased breath sounds in the left infraclavicular area laterally. Imaging studies revealed a peripheral thick-walled left upper lobe cavitary lesion, left lower lobe consolidation and an enlarged subcarinal lymph node. She was treated with doxycycline for 10 days without improvement. Pertinent laboratory tests, microbiologic workup and fibre-optic bronchoscopy were non-diagnostic and a CT-guided left upper lobe lung biopsy revealed acute fibrinous organising pneumonia. She was treated with azithromycin with complete resolution of symptoms. To our knowledge, this is the first reported case of acute fibrinous organising pneumonia presenting as a cavitary lung lesion and the first with treatment response to azithromycin.